Perlindungan Hak Asasi Manusia Menurut Hadits Riwayat Al-Bukhori Dan UUD 1945 Pasal 28 (International Forum of Researchers and Lecturers, 2024)
Human rights are rights given to every person. Human rights first emerged as a result of resistance to government absolutism towards its citizens. The purpose of this normative legal study is to provide an explanation of secondary evidence collected through a literature survey. In Indonesia, the government continues to try to balance religious values with human rights. Primary legal sources related to human rights as well as secondary legal materials in the form of literature and professional opinions on these topics are included in the secondary data of this study. The value, quality and condition of the data collected were considered during the comparative descriptive analysis of the data collected. The quality, value and condition of the relevant data were measured and used as the foundation of this research. With the research methodology used, the findings and analysis of this research are expected to answer the research question of human rights protection in the view of hadith and the 1945 Constitution article 28, while taking into consideration the viewpoints of both national law and hadith. Islamic law is built on a solid and complete structure because it comes from Allah, the Almighty, the Most Praiseworthy. It shows and conveys all the benefits of the world and the hereafter. The relationship between the Hadith view and Article 28 of the 1945 Constitution shows the relationship between religious teachings and positive law in an effort to protect human rights